Pengaruh Suhu dan Konsentrasi Monomer Pada Polimerisasi Asam Tanat Sebagai Zat Warna Terhadap Efisiensi Dye Sensitized Solar Sel - Agustini, Dwi; Hardeli, Hardeli (Jurusan Kimia FMIPA UNP, 2019)
Dye Sensitized Solar Cell (DSSC) is a solar cell with a dye as an absorbent of photons from sunlight. Research related to DSSC is still ongoing to find DSSC components that produce high efficiency, but are easy and inexpensive to produce. Polymerization is a combined reaction of several monomers with certain rearrangements. The polymerized monomer is tannic acid which is an organic compound that has about 20 Ï€-Ï€ * bonds. The tannic acid produced is then used as a dye in the DSSC circuit. Assembled DSSCs are tested for voltage and resistance using a digital multimeter. The polymerized dyes were characterized using UV-Vis, FTIR. The results of the UV-Vis analysis showed that the batochromic shift occurred in the polymerized dye. The batochromic effect will cause more photons to be converted into electrical energy. The FTIR spectrum is used to confirm the formation of poly-tannic acid. The efficiency of DSSC with polymerized dyes was higher than that of non-polymerized dyes, which was 8.9%